2018
DOI: 10.3310/phr06110
|View full text |Cite
|
Sign up to set email alerts
|

The impact of home energy efficiency interventions and winter fuel payments on winter- and cold-related mortality and morbidity in England: a natural equipment mixed-methods study

Abstract: Background England, and the UK more generally, has a large burden of winter- and cold-related mortality/morbidity in comparison with nearby countries in continental Europe. Improving the energy efficiency of the housing stock may help to reduce this, as well as being important for climate change and energy security objectives. Objectives To evaluate the impact of home energy efficiency (HEE) interventions on winter- and cold-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(51 citation statements)
references
References 100 publications
1
50
0
Order By: Relevance
“…More recently, Armstrong et al [27] have developed an empirical study, also considering the main pathways. The author's aim was to determine which sets of energy efficiency measures affect energy and health outcomes, i.e., how changes in housing energy efficiency measures impact different categories of health outcomes.…”
Section: Relevance Of Housing Energy Efficiency For Health Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, Armstrong et al [27] have developed an empirical study, also considering the main pathways. The author's aim was to determine which sets of energy efficiency measures affect energy and health outcomes, i.e., how changes in housing energy efficiency measures impact different categories of health outcomes.…”
Section: Relevance Of Housing Energy Efficiency For Health Outcomesmentioning
confidence: 99%
“…While the main health outcomes have been associated with cardiorespiratory conditions, winter mortality and morbidity, thermal comfort, psychosocial wellbeing and nutrition outcomes. Additionally, to be associated to different efficiency pathways, these outcomes have also been classified according to their time horizon, as short term /immediate or long-term impacts (timeframe greater than 10 years) [27]. Figure 1 represents an approach which emphasises the need not only to assess health outcomes associated to already established energy efficiency pathways, as proposed by Willand et al [26] but also to study this association throughout time, as suggested by Armstrong et al [27].…”
Section: Relevance Of Housing Energy Efficiency For Health Outcomesmentioning
confidence: 99%
See 3 more Smart Citations